PENERAPAN PEMBELAJARAN GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X IPA 1 MAN 2 BANYUWANGI - Haridi, Haridi (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Based on preliminary study, it is known that the students of class XIPA 1 MAN 2 Banyuwangi have problems in the learning process ofmathematics. Therefore, teachers need to seek solutions. Theteacher's efforts include applying cooperative learning model ofGroup investigation type. This study aims to determine: 1) Increasedmotivation and learning activities of mathematics throughcooperative learning model type of gruop investigation on studentsclass X IPA 1 MAN 2 Banyuwangi. 2) improving mathematicslearning outcomes through cooperative learning model type of gruopinvestigation on students class X IPA 1 MAN 2 Banyuwangi. Thisresearch is a classroom action research conducted on the subject ofMathematics. Subjects in the meticulous are students of Class X IPA1 MAN 2 Banyuwangi academic year 2017/2018. The researchprocedure consists of two cycles for 4 meetings. Each cycle iscarried out with activities: Planning, Action Implementation,Observation, Evaluation, Reflection. Analytical technique that willbe used is descriptive technique. The results showed: 1) there is anincrease in motivation and learning activities of mathematicsthrough cooperative learning model type of gruop investigation instudents of class X IPA 1 MAN 2 Banyuwangi. 2) there isimprovement of mathematics learning outcomes through cooperativelearning model type of gruop investigation in students of class XIPA 1 MAN 2 Banyuwangi.